The Influence of the PhET Simulation-Assisted Project-Based Learning Model on Students' Ability to Master the Elasticity Concept - Dian Faisal Hadi; Aris Doyan; Ahmad Harjono; Jannatin ‘Ardhuha (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the effect of the PhET simulation-assisted project-based learning model on students' ability to master the concept of elasticity.  The type of research used in this study was a quasi-experimental design with a pre-test and post-test control group design.  The population in this study were all students of class XI IPA at SMAN 1 Wanasaba East Lombok, totaling 142 students.  The research sample was taken using purposive sampling, so that 31 students were selected in class XI IPA 2 as the experimental class and 31 students in XI IPA 1 as the control class.  The independent variable in this study was the PhET simulation-assisted project-based learning model used in the experimental class, while the ability to master the concept became the control variable.  The instrument used to measure the students' mastery of the concept is a test instrument in the form of a description test on the material elasticity of 6 questions.  The results of the pre-test data analysis showed that the students' initial knowledge was almost the same, but after being given treatment, the average post-test score of the experimental class was 79.22 and that of the control class was 72.64.  The results of the t test using the Independent Sample T test on the post-test showed a significance (2 tailed) less than 0.050, so it can be concluded that the project-based learning model assisted by the PhET simulation has an effect on students' ability to master the concept of elasticity.